Mengkaji Ulang Pola Pemberdayaan Suku Anak Dalam Di Provinsi Jambi - Pratama, Fikri Surya (Program Studi Pengembangan Masyarakat Islam, 2023)
Various kinds of empowerment programs for the Suku Anak Dalam have been carried out. This empowerment involves various parties such as the government, the Anak Dalam Tribe caring community, religious da'wah groups, and private companies engaged in oil palm plantations. Some empowerment programs are seen as having a suboptimal impact in terms of sustainability. Therefore, this paper aims to review what causes the results of this empowerment program to be not optimal, and how to solve them. This research is qualitative in nature with analytical reporting. Methods of data collection by interviews with two informants and observations, where the sources of data that have been collected, then analyzed with a anthropology approach, reduced by comparing data with each other, then presented and conclusions drawn. The results of this study are realizing how important it is to disseminate information regarding the progress and development of SAD life in society. It is the duty of the government, NGOs, educational institutions to disseminate information, not just material knowledge, but an injection of affection. This is intended to create an emotional connection from people outside the Anak Dalam Tribe to find out how life for SAD will improve if empowered together, as well as to minimize the negative connotations and treatment that apply to SAD so far. By strengthening the roots of knowledge and affection for each other's sensitivity to issues, and willing to work together for mutual tolerance and hand in hand, the empowerment program can run well and be sustainable in the long term. The empowerment program must also pay attention to the locality and participatory aspects of the Anak Dalam tribe itself. If in the past the focus was on physical development, the later stages of empowerment are on psychological empowerment and soft skills and hard skills.